Attempts to produce blast furnace coke from Victorian brown coal. 2. Hot briquetting, air curing and higher carbonization temperature. (1st June 2016) - Mollah, M. Mamun; Marshall, Marc; Jackson, W. Roy; Chaffee, Alan L.
Highlights: Hot briquetting and air curing caused significant increase in compressive strength. Hot briquetting reduced the reactivity. High carbonization temperature reduced reactivity and surface area. The proportion of graphitic structure remained small. Compressive strength and reactivity remained higher than those of a typical BF coke. Abstract: Attempts have been made to obtain a substitute for blast furnace (BF) coke from a Victorian brown coal mixed with a tar derived from brown coal under conditions sufficiently mild to be economical. Changes to the procedure used in a previous attempt include hot briquetting of the coal–tar mixture at 150 °C rather than ambient, the addition of air curing at 200 °C and carbonization at higher temperature, 1200 °C, rather than 900–950 °C. All these changes led to a decrease in reactivity and increase in compressive strength. In addition, the higher carbonization temperature led to a decrease in surface area. Thus the combined changes led to an increase in strength and decrease in reactivity and surface area. This is the first time a carbonized product has been prepared from brown coal in good yield and of lower reactivity than brown coal char when compared with BF coke. However, the reactivity and surface area remain too high for the product to be used as a substitute for BF coke.